Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Insurance and Pension Sectors. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on the insurance and pension sectors. The governance, accountability, and internal processes of the supervisors, operating under a well-functioning twin-peaks model, are robust. With two-tier boards that include independent members, and an internal audit department, the governance structure of both supervisors is vigorous. Detailed documentation supports the internal processes. Discussions are underway to determine a new structure for the pension system, which may include shifting risks to the participants.